Marketing strategy of ppsdm kebtke as public service agency - Juni Ferson, Nico; Rudito, Bambang (The Indonesian Journal of Business Administration, 2018)
Human Resources Development Center For Electricity, New Energy, Renewable And Energy Conservation (PPSDM KEBTKE) is a training institution under the Ministry of Energy and Mineral Resources which has the duty and function to educate and train Human Resources in Electricity, New Energy, Renewable And Energy Conservation which previously serving in the internal environment only Ministry of Energy and Mineral Resources and in 2018 changed to the Public Service Agency based on Decree of the Minister of Finance No. 965 / KMK / .05 / 2017 on December 27, 2017 and is expected to improve services and to provide services to the community and in conducting its activities based on the principle of efficiency and productivity, but the condition of this change has a very big challenge because previously PPSDM KEBTKE has never done business practice and not yet known, so that PPSDM KEBTKE known and get the market then needed the right marketing strategy.This study used a qualitative approach where the primary data is taken from both internal and external interviews and for secondary data obtained through supporting literature. From the results of this research analysis found that PPSDM KEBTKE currently not maximized in marketing and approaches to consumers who become the target, then from this research obtained some strategies to improve consumer awareness and strengthen PPSDM KEBTKE to be known and excel in the competition. Keywords: Training, Public Service Agency, Marketing Strategy, Qualitative, external, internal